Extracellular vesicles from specific muscle progenitor cells as a novel therapeutic strategy for sarcopenia - Bi Zhao; Yao Yao; Hong Shi; Srinivas M. Tipparaju; Muhammad Ashraf; Wanling Xuan (Stem Cell Research & Therapy, 2026)
Abstract Background Sarcopenia, characterized by age-related loss of skeletal muscle mass and function, poses a significant challenge to lifelong health and wellbeing. Currently, no effective therapeutic interventions exist. In previous work, we developed specialized muscle progenitor cells (MPCs), termed Givi-MPC, from human induced pluripotent stem cells (hiPSCs). These cells demonstrated robust regenerative capacity in both sarcopenic and dystrophic muscle models. However, the potential of extracellular vesicles (EVs) derived from Givi-MPC to rejuvenate aged muscle stem cells (MuSCs) and their niche remains unexplored. This study investigates the therapeutic efficacy of EVs derived from Givi-MPC in sarcopenia. Methods Givi-MPC were generated from hiPSCs using CHIR990021 and givinostat. EVs were isolated from Givi-MPC or primary human myoblast via size exclusion chromatography and characterized by transmission electron microscopy (TEM), Western blotting, and tandem mass tag (TMT)-based mass spectrometry. Aged C57BL/6J mice (24–25 months old) received intramuscular administration of EVs derived from Givi-MPC, and therapeutic efficacy was assessed through grip strength testing, immunohistochemistry, metabolic profiling, and spatial transcriptomics. To evaluate regenerative capacity, aged MuSCs treated with EVs-Givi-MPC or phosphate-buffered saline (PBS) were subjected to in vitro myogenic differentiation and transplanted into mdx/scid mice following cardiotoxin-induced muscle injury. Results Proteomic analysis revealed that EVs derived from Givi-MPC were enriched in proteins associated with regeneration, angiogenesis, axonal repair, and cellular homeostasis compared to EVs from primary human myoblasts. Treatment with EVs-Givi-MPC significantly increased muscle mass and strength, reduced muscle degeneration, enhanced angiogenesis and reprogrammed the metabolic landscape of aged muscle. EVs-Givi-MPC treatment enhanced clonal expansion and myogenic differentiation of isolated aged MuSCs. Upon transplantation, MuSCs pretreated with EVs-Givi-MPC generated more dystrophin⁺/Myh3⁺ cells at day 5 and a greater number of dystrophin⁺ fibers at day 30 compared to PBS treated controls. Spatial transcriptomics and immunostaining indicated that Givi-MPC EVs reversed MuSCs senescence and reprogrammed their transcriptomic profile toward self-renewal and differentiation, while restoring niche signaling to a more youthful state. Conclusions EVs derived from Givi-MPC improve muscle mass, fiber cross-sectional area, and grip strength, effectively rejuvenate aged MuSCs and their microenvironment. These findings support the potential of EV-based therapies as a novel approach for treating sarcopenia.